S65 The role of Src kinase in inspiratory resistive breathing-induced pulmonary inflammation. (12th November 2015) - Toumpanakis, D; Zacharatos, P; Michailidou, T; Tsoukalas, G; Vassilakopoulos, T
Abstract : Introduction and objectives: Inspiratory resistive breathing (IRB), a hallmark of obstructive pulmonary diseases, is characterised by large negative intrathoracic pressures. IRB is shown to induce pulmonary inflammation in previously healthy rats. Src is a multifunctional kinase that is activated by phosphorylation upon mechanical stress and plays a significant role in inflammatory processes. The aim of our study was to investigate the role of Src in IRB-induced pulmonary inflammation. Methods: Anaesthetised, tracheostomised rats were breathing spontaneously through a 2-way non rebreathing valve. The inspiratory port was connected to a resistance, setting peak tidal tracheal pressure at 50% of maximum (IRB). Quietly breathing animals served as controls. After 6 h of IRB, the mechanics of the respiratory system were assessed with the forced oscillation technique. Bronchoalveolar lavage (BAL) was performed to measure total and differential cell count and total protein levels. Phosphorylation of Src and ERK was detected in lung tissue samples by Western blot analysis at 30 min, 3 and 6 h of IRB. The Src inhibitor PP2 was administered intraperitoneally (1 mg/kg), 30 min prior to IRB, in a subgroup of animals. Results: After 6 h of IRB, increased tissue elasticity was measured, compared to control. Increased BAL cellularity was also found (2-fold increase to control), due to raised numbers of both macrophages and neutrophils. Total protein levels were elevated in BAL fluid. Src activation was detected at 30 min of IRB (3-fold increase to control), while ERK was phosphorylated at 3 and 6 h. Inhibition of Src kinase attenuated the increase in tissue elasticity after 6 h of IRB. Following inhibition of Src kinase, the total cell number after 6 h of IRB was not increased compared to control. Neither macrophage nor neutrophil count was elevated after 6 h of IRB, following Src inhibition. Total protein levels were not altered by Src inhibition. Src inhibition attenuated the activation of ERK only at 3 h of IRB. Conclusion: Src kinase activation partly mediates IRB-induced pulmonary inflammation.